Outcome of lesional epilepsy surgery: Report of the first comprehensive epilepsy program in Iran. Issue 4 (August 2019) - Mehvari Habibabadi, Jafar; Moein, Houshang; Basiratnia, Reza; Badihian, Shervin; Zaki, Bagher; Manouchehri, Navid; Zare, Mohammad; Barekatain, Majid; Rahimian, Elham; Mehvari Habibabadi, Amirali; Moein, Payam; Aghakhani, Yahya; et al.
Abstract : Background: We investigated the utility of epilepsy surgery and postoperative outcome in patients with lesional epilepsy in Iran, a relatively resource-poor setting. Methods: This prospective longitudinal study was conducted during 2007–2017 in Kashani Comprehensive Epilepsy Center, Isfahan, Iran. Patients with a diagnosis of intractable focal epilepsy, with MRI lesions, who underwent epilepsy surgery and were followed up ≥ 24 months, were included and evaluated for postoperative outcome. Results: A total of 214 patients, with a mean age of 26.90 ± 9.82 years (59.8% men) were studied. Complex partial seizure was the most common type of seizure (85.9%), and 54.2% of the cases had auras. Temporal lobe lesions (75.2%) and mesial temporal sclerosis (48.1%) were the most frequent etiologies. With a mean follow-up of 62.17 ± 19.33 months, 81.8% of patients became seizure-free postoperatively. Anticonvulsants were reduced in 86% of the cases and discontinued in 40.7%. In keeping with previous studies, we found that seizure freedom rates were lower among patients with longer follow-up periods. Conclusions: We found high rates of seizure freedom after surgery in lesional epilepsy patients despite limited facilities and infrastructure; antiepileptic medications were successfully tapered in almost half of the patients. Considering the favorable outcome of epilepsy surgery in our series, we believe that it is a major treatment option, even in less resource-intensive settings, and should be encouraged. Strategies to allow larger scale utility of epilepsy surgery in such settings in the developing world and dissemination of such knowledge may be considered an urgent clinical need, given the established mortality and morbidity in refractory epilepsy.